Fatigue behaviour of a polymer concrete with and without added polyester fibre / Omar Bapokutty - Bapokutty, Omar (2006)
The fatigue and fracture behavior of polymer concrete has been studied. The study has been conducted on polymer concrete plates with and without notch under fatigue loading of constant amplitude (Fa = 0.05 kN) and at frequency of 25 Hertz. The fatigue resistant of polymer concrete material reinforced with waste polyester fibers was also studied and compared with the former composite. The polymer concrete used in this study was a series of formulated composite with ratio of 60:30:10 of sand, polyester resin and talcum powder respectively. For a fiberreinforced polymer concrete, 0.25 percent waste polyester fiber mixture was added and 59.75 percent reduction of sand was formulated. Polymer concrete has been found to exhibit better fatigue and fracture properties than the Portland Cement. The addition of fiber to the polymer concrete showed an increased in the fatigue resistant about 5% for without notch and 20% for notch specimens. Introducing precrack to the specimens (a/w = 4/22) reduced its fatigue resistant up to 6% for polymer concrete and up to 3% for fiber-reinforced polymer concrete. This is attributed to crack formation in the material during the specimen’s preparation. The addition of fibers to the polymer concrete was found to enhance the crack resistance of the composite. The improvement in fatigue life by the addition of fiber was the fibers acted as barriers to the crack growth and its propagation.